Altruistic Scheduling in Multi-Resource Clusters - Grandl, Robert; Chowdhury, Mosharaf; Akella, Aditya; Ananthanarayanan, Ganesh (USENIX OSDI, 2016)
Given the well-known tradeoffs between fairness, performance, and efficiency, modern cluster schedulers often prefer instantaneous fairness as their primary objective to ensure performance isolation between users and groups. However, instantaneous, short-term convergence to fairness often does not result in noticeable long-term benefits. Instead, we propose an altruistic, long-term approach, CARBYNE, where jobs yield fractions of their allocated resources without impacting their own completion times. We show that leftover resources collected via altruisms of many jobs can then be rescheduled to further secondary goals such as application-level performance and cluster efficiency without impacting performance isolation. Deployments and large-scale simulations show that CARBYNE closely approximates the stateof-the-art solutions (e.g., DRF) in terms of performance isolation, while providing 1.26× better efficiency and 1.59× lower average job completion time.